2013
DOI: 10.1073/pnas.1220645110
|View full text |Cite
|
Sign up to set email alerts
|

Increased photosystem II stability promotes H2production in sulfur-deprivedChlamydomonas reinhardtii

Abstract: Photobiological H 2 production is an attractive option for renewable solar fuels. Sulfur-deprived cells of Chlamydomonas reinhardtii have been shown to produce hydrogen with the highest efficiency among photobiological systems. We have investigated the photosynthetic reactions during sulfur deprivation and H 2 production in the wild-type and state transition mutant 6 (Stm6) mutant of Chlamydomonas reinhardtii. The incubation period (130 h) was dissected into different phases, and changes in the amount and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 39 publications
13
114
0
Order By: Relevance
“…Additionally, this faster transition from aerobic to anaerobic conditions in sulfur-depleted stm6 cultures was recently proposed to reduce the exposure time of PSII to reactive oxygen species formed in sulfur-deprived cells when the PSII repair cycle is impaired. In this study, a higher residual PSII activity was seen for stm6 within the anaerobic phase and suggested as an explanation for the higher hydrogen production capacity, since both wild type and stm6 maintained electron flow to the hydrogenase by water-splitting and linear electron transport (Volgusheva et al, 2013). However, several studies demonstrated the competition between cyclic electron flow and hydrogen production in C. reinhardtii (Tolleter et al, 2011;Steinbeck et al, 2015), and the inability of stm6 to switch from linear to cyclic electron flow under anaerobic conditions (Kruse et al, 2005) should largely contribute to its elevated hydrogen production capacity.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Additionally, this faster transition from aerobic to anaerobic conditions in sulfur-depleted stm6 cultures was recently proposed to reduce the exposure time of PSII to reactive oxygen species formed in sulfur-deprived cells when the PSII repair cycle is impaired. In this study, a higher residual PSII activity was seen for stm6 within the anaerobic phase and suggested as an explanation for the higher hydrogen production capacity, since both wild type and stm6 maintained electron flow to the hydrogenase by water-splitting and linear electron transport (Volgusheva et al, 2013). However, several studies demonstrated the competition between cyclic electron flow and hydrogen production in C. reinhardtii (Tolleter et al, 2011;Steinbeck et al, 2015), and the inability of stm6 to switch from linear to cyclic electron flow under anaerobic conditions (Kruse et al, 2005) should largely contribute to its elevated hydrogen production capacity.…”
supporting
confidence: 49%
“…Higher rates of dark respiration in acetate-containing media have been observed before (Kruse et al, 2005) and were proposed to represent one of the main reasons for the rapid induction of photosynthetic hydrogen production in this mutant (Nguyen et al, 2011;Volgusheva et al, 2013). Considering the effect of a MOC1 inactivation on mitochondrial nd1 expression (Wobbe and Nixon, 2013;Fig.…”
Section: Light Stress Induces a Switch From The Energy-dissipating Tomentioning
confidence: 81%
See 1 more Smart Citation
“…As the efficiency of substrate supply is the major bottleneck in H 2 production with microalgae (Kruse and Hankamer, 2010), reduced availability of protons and electrons derived from the water-splitting reaction at PSII should result in a perturbation of hydrogen production activity. Recently, Volgusheva et al (2013) showed that the amount of active PSII during the hydrogen production phase is directly correlated to the amount of H 2 generation. This could mean that in the absence of LHCBM9 and the concomitant higher production of ROS, photoinhibitory damage of PSII is more pronounced, therefore leading to lower overall amounts of H 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Tests are still limited to the lab, but according to some researchers, growing microalgae able to produce H2 has great promise for generating large-scale sustainable energy (e.g. [130][131][132][133][134]). However, many technical limitations exist, hindering the exploitation of this potential resource (e.g., algal physiology, metabolic issues) [130,131].…”
Section: Third-generation: Algaementioning
confidence: 99%